2021
DOI: 10.1177/1539449220984110
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Exergaming in Home-Based Pediatric Constraint-Induced Therapy: A Randomized Trial

Abstract: Constraint-induced therapy (CIT) is highly effective yet not accessible to many families. Integrating commercial exergaming in home-based CIT may support the availability and attainability of the intervention. The study compared the effects of supplementary use of Nintendo Wii in home-based CIT with dose-equivalent conventional CIT. Eighteen children with cerebral palsy were randomly assigned to 8 weeks of CIT (CIT) or 4 weeks of CIT, followed by 4 weeks of Wii-augmented CIT (CIT-Wii). Outcome measures include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(58 citation statements)
references
References 35 publications
0
58
0
Order By: Relevance
“…Recent research using this console to treat patients with CP has shown positive effects compared to other kinds of rehabilitation services. 55-57…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research using this console to treat patients with CP has shown positive effects compared to other kinds of rehabilitation services. 55-57…”
Section: Discussionmentioning
confidence: 99%
“…Recent research using this console to treat patients with CP has shown positive effects compared to other kinds of rehabilitation services. [55][56][57] This will be the first study assessing the effects of a six-week exercise programme remote (TR) using a Nintendo Wii balance board to improve standing balance in children and adolescents with CP type spastic hemiplegia compared with the effects of an FtF modality. This trial will provide evidence on the effectiveness of the Nintendo Wii for improving standing balance in patients with CP, a matter in which the current evidence is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The main evidence on rehabilitation services that can be delivered by telemedicine concerns: the televisit -> which can increase access to specialist visits at a low cost and from remote locations, ensuring high levels of caregiver satisfaction and the remote reproducibility of the assessment of some of the key clinical parameters [ 21 , 22 , 23 , 24 ]; synchronous and asynchronous telecounseling -> improves the usability of services and caregiver satisfaction, with evidence of non-inferiority to the traditional treatment of infantile cerebral palsy and GCA [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ] and showing potential efficacy. However, there is need for further clinical studies; telecounseling -> has been shown to be effective on the behavior of children with disabilities, particularly by intervening with parents with respect to the performance of the Home Exercise Program (HEP) [ 23 , 31 ]; telemonitoring -> device-based and/or video-call-based; it can potentially provide feedback to healthcare professionals and patients, in order to modify the individual rehabilitation plan, and increase engagement and adherence to HEP [ 32 , 33 ].…”
Section: Telemedicine At Homementioning
confidence: 99%
“…synchronous and asynchronous telecounseling -> improves the usability of services and caregiver satisfaction, with evidence of non-inferiority to the traditional treatment of infantile cerebral palsy and GCA [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ] and showing potential efficacy. However, there is need for further clinical studies;…”
Section: Telemedicine At Homementioning
confidence: 99%
“…Some psychosocial benefits in terms of decreased parental stress and increased child engagement were found. However, as Wii games were not designed for therapeutic use, it might not provide appropriate grading methods for the rehabilitative goal ( Wang et al, 2021 ). The Kinect camera is a low-cost and portable markerless motion capture sensor.…”
Section: Introductionmentioning
confidence: 99%